Notable individuals of British communism, 1886-1997. - Communist Party of Great Britain; Communist Party of Great Britain. Archive Trust (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
This collection is drawn from the personal papers of a multitude of CPGB activists throughout the twentieth century. This includes those at the heart of party (such as full-time "national organisers") and peripheral figures who supported the communist cause (such as Labour MP Dennis Nowell Pritt). Covering over a hundred years, from the communist movement's earliest sprouting's to its nadir in the late twentieth century, the collection offers valuable insights into the grassroots efforts of almost one hundred communist activists and sympathisers.
Date range: 1886-1997.
Keywords: Communist Party of Great Britain; Political activists -- Great Britain; Communism -- Great Britain